Case report: L5 tomita En bloc spondylectomy for oligometastatic liposarcoma with post adjuvant stereotactic ablative radiotherapy - Saha, Priyanshu; Raza, Mohsen; Fragkakis, Angelo; Ajayi, Bisola; Bishop, Timothy; Bernard, Jason; Miah, Aisha; Zaidi, Shane H.; Abdelhamid, Mohamed; Minhas, Pawan; Lui, Darren F. (Frontiers in Surgery, 2023)
Introduction: Tomita En-bloc spondylectomy of L5 is one of the most challenging techniques in radical oncological spine surgery. A 42-year-old female was referred with lower back pain and L5 radiculopathy with a background of right shoulder liposarcoma excision. CT-PET confirmed a solitary L5 oligometastasis. MRI showed thecal sac indentation hence wasn’t suitable for Stereotactic Ablative Radiotherapy (SABR) alone. The seeding nature of sarcoma prevents the indication of separation surgery hence excisional surgery is considered for radical curative treatment. This case report demonstrates dual-staged modified TES including the utilisation of novel techniques to allow for maximum radical oncological control in the era of SABR and lesser invasive surgery. Methods: First-stage: Carbonfibre pedicle screws planned from L2 to S2AI-Pelvis, aligned, to her patient-specific rods. Radiofrequency ablation of L5 pedicles prior to osteotomy was performed to prevent sarcoma cell seeding. Microscope-assisted thecal sac tumour separation and L5 nerve root dissection was performed. Novel surgical navigation of the ultrasonic bone-cutter assisted inferior L4 and superior S1 endplate osteotomies. Second-stage: Vascular-assisted retroperitoneal approach at L4-S1 was undertaken protecting the great vessels. Completion of osteotomies at L4 and S1 to En-bloc L5: (L4 inferior endplate, L4/5 disc, L5 body, L5/S1 disc and S1 superior endplate). Anterior reconstruction used an expandable PEEK cage obviating the need for a third posterior stage. Reinforced with a patient-specific carbon plate L4-S1 promontory. Results: Patient rehabilitated well and was discharged after 42 days. Cyberknife of 30Gy in 5 fractions was delivered two months post-op. Despite left foot drop, she’s walking independently 9 months post-op. Conclusion: These are challenging cases require a truly multi-disciplinary team approach. We share this technique for a dual stage TES and metal-free construct with post adjuvant SABR to achieve maximum local control in spinal oligometastatic disease. This case promotes our modified TES technique in the era of SABR and separation surgery in carefully selected cases.